Zelle : Schwarz auf Weiss. - Bainchi, Paolo; Zinggl, Wolfgang (Wien : Galerie Theuretzbacher, 1994)
Ammann, Gerry ; Bender, Wolfgang ; Buttinger, Andreas ; Brunner, Hannes ; Collyer, Robin ; Eckhardt, Friedrich ; Flois, Herbert ; Friedl, Peter ; Gallée, Ilia ; Honory, Alexander ; Huyghe, Philip ; Kern, Josef ; etc.
Ausstellung "Zelle", Galerie Theuretzbacher, Wien, Dez. '94 - Jan. '95
Duits
kunstcatalogus